2005
DOI: 10.2307/3588524
|View full text |Cite
|
Sign up to set email alerts
|

Motivators That Do Not Motivate: The Case of Chinese EFL Learners and the Influence of Culture on Motivation

Abstract: Language learning motivation plays an important role in both research and teaching, yet language learners are still largely understood in terms of North American and European cultural values. This research explored language learning motivation constructs in a Chinese cultural setting, where large numbers of students are required to study English. In Taiwan, 567 language learners responded to a survey concerning motivation orientation, expectancy, and self‐evaluated skill. Factor analysis and structural equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
148
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 44 publications
10
148
5
2
Order By: Relevance
“…The findings of some studies on language learning motivation have even contradicted that of a previous study on a similar subject in the same context (Lamb, 2007). Some other studies have exclusively aimed at describing the motivational patterns of the participants rather than proving whether certain kinds of motivation can guarantee success in learning English as a second language (ess e.g., Rahman, 2005;Chen et al, 2005).…”
Section: Introductioncontrasting
confidence: 47%
See 1 more Smart Citation
“…The findings of some studies on language learning motivation have even contradicted that of a previous study on a similar subject in the same context (Lamb, 2007). Some other studies have exclusively aimed at describing the motivational patterns of the participants rather than proving whether certain kinds of motivation can guarantee success in learning English as a second language (ess e.g., Rahman, 2005;Chen et al, 2005).…”
Section: Introductioncontrasting
confidence: 47%
“…Although numerous research studies have been conducted on motivation in SLA within the past ten years, most of these studies that have been done in Asia such as in China and Hong Kong (Liu, 2007;Wang, 2007;Wei, 2007;Wu Man fat, 2007;Yihong et al, 2007) and others in South Asia (Rahman, 2005), Southeast Asia (Lamb, 2007), Southwest Asia (Balkir and Topkaya, 2009), or East Asia (Guilloteaux and Dörnyei, 2008;Melendy, 2008;Wu and Wu, 2008;Takase, 2007;Chen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Mori (2002) concluded that "foreign language reading motivation closely resembles more general forms of motivation as laid out in expectancy-value theory" (p. 102). Concerning integrative motivation, the results of Mori's study were consistent with other motivational research (Chen, Warden, & Chang, 2005;Crookes & Schmidt, 1991;Dörnyei, 1990;Kraemer, 1993) conducted in EFL contexts and did not to find the significance of integrative motivation as Gardner suggested. However, given the globalization trend, it is very likely that the English major freshmen, who will be the potential participants of the current project, would have the desire to integrate with the target language culture.…”
Section: Motivation To Read In Second/foreign Languagesupporting
confidence: 81%
“…Chen et al (2005) in a study on Taiwanese students' language learning motivation even added one more category, the required orientation, to the two existing categories, the integrative orientation and instrumental orientation, to signify the important role tests have played in most Taiwanese students' language learning experience. With this exam-oriented tradition, it was not surprising to see that the Ministry of Education (MOE) of Taiwan Challenge 2008: National Development Plan featured ten key individual plans including "e-generation manpower cultivation plan," which aimed to cultivate e-generation manpower with good IT, English, and creative skills.…”
Section: Introductionmentioning
confidence: 99%